Design and simulation of series loaded resonant converter / Aizatul Azlin Ghazali - Ghazali, Aizatul Azlin (2010)
The title of this project is Design and Simulation of Series Loaded Resonant Converter. Basically, this thesis includes the design techniques and simulation of the series loaded resonant converter operating above resonance. The half-bridge series loaded resonant topology is considered in this paper. This converter had been designed based on I00 kHz switching frequency with variation of input voltage of 50V ± 20%. From the voltage conversion ratio, v o v i n curve, the desired natural frequency, <JJ0 can be determined by approximate the value of W o which is 1.1. The value of resonant frequency lo can be determined. The result shows that the tank circuit (L and C) is maintained in the continuous conduction mode which gives sinusoidal waveform. Detailed circuit simulation is carried out using PSIM simulation package to verify the circuit operation. Thus, the simulation results and theoretical value can be compared.